2006
DOI: 10.1176/appi.ajp.163.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Negative Signs and Symptoms Secondary to Antipsychotics: A Double-Blind, Randomized Trial of a Single Dose of Placebo, Haloperidol, and Risperidone in Healthy Volunteers

Abstract: Single doses of both haloperidol and risperidone produce negative symptoms in normal individuals. Drowsiness may be an important confounding factor in the assessment of negative symptoms in antipsychotic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 26 publications
5
76
1
2
Order By: Relevance
“…dopaminergic antagonist infusion either systemically 100 , or within the nucleus accumbens 101 substantially reduces response vigor in food seeking behavior or, otherwise bias action selection away from effortful choices, even when reward offers are considered worthy. It is well known that patients under high dopamine receptor antagonism can display severe apathetic behavior 102 . Further support for this notion is found in non-primate research on drug seeking behavior reinstatement, which is a suitable model of drug addiction relapse after a period of abstinence 103 .…”
Section: Ventromedial Prefrontal Cortex and Dopamine: Decoding Decisimentioning
confidence: 99%
“…dopaminergic antagonist infusion either systemically 100 , or within the nucleus accumbens 101 substantially reduces response vigor in food seeking behavior or, otherwise bias action selection away from effortful choices, even when reward offers are considered worthy. It is well known that patients under high dopamine receptor antagonism can display severe apathetic behavior 102 . Further support for this notion is found in non-primate research on drug seeking behavior reinstatement, which is a suitable model of drug addiction relapse after a period of abstinence 103 .…”
Section: Ventromedial Prefrontal Cortex and Dopamine: Decoding Decisimentioning
confidence: 99%
“…However, studies of healthy volunteers offer indications. Artaloytia et al (2006) reported that single doses of haloperidol, and particularly of risperidone, produced negative symptoms in healthy volunteers. Park et al (2012) likewise found that a single dose of risperidone induced negative symptoms (including increased avolition), although they concluded that haloperidol, amisulpride and aripiprazole did not.…”
Section: Medication and Boredommentioning
confidence: 99%
“…Ausgeprägte extrapyramidale Störungen sind zwar seit der Einführung der Antipsychotika der zweiten Generation und vorsichtigeren Dosierungsrichtlinien seltener geworden. Man darf jedoch nicht unterschätzen, dass auch diskrete extrapyramidale Symptome für Negativsymptome g ehalten werden können und daher bei der Diagnostik berücksichtigt werden sollten [29,30] [34].…”
Section: Primäre Versus Sekundäre Negativsymptomeunclassified